Preliminary damage and loss assessment Yogyakarta and central Java natural disaster : The 15th Meeting of The Consultative group on Indonesia Jakarta, June 14 2006 - Bappenas (Jakarta:Bappenas, 2006)
Koleksi Referensi (Tidak Dipinjamkan)